Leprosy and the serodiagnostic test for tuberculosis. Issue 8 (August 1977) - Cruickshank, J G; Ellis, B P
Abstract : Sera from patients with leprosy agglutinated killed H37Rv Mycobacterium tuberculosis to varying degrees. Higher titres were found in association with active disease but there was no difference between patients at the lepromatous or at the tuberculoid ends of the clinical scale. A sharp rise in titre occurred during the active phase of an episode of erythema nodosum leprosum.